FACTORS OF ECOLOGICAL STATE FORMING FOR URBANIZED ENVIRONMENT - Франчук, Г.; Гроза, В.; Маджд, С. (Proceedings of National Aviation University (archive), 2012)
Impact of enterprises for exploitation and repair of aviation techniques on soil state in zone of airport hasbeen investigated. Technical and ecological characteristic of an airport located within city territory has beendone. Monitoring of soils on territories near aviaenterprises has been carried out. The most important factorsfor soil toxicity has been determined. Assessment of summary effect of these factors has been done